Conjugative IncC Plasmid Entry Triggers the SOS Response and Promotes Effective Transfer of the Integrative Antibiotic Resistance Element SGI1 - Marine C. Pons; Karine Praud; Sandra Da Re; Axel Cloeckaert; Benoît Doublet (Microbiology Spectrum, 2023)
ABSTRACT The broad-host-range IncC plasmid family and the integrative mobilizable Salmonella genomic island 1 (SGI1) and its derivatives enable the spread of medically important antibiotic resistance genes among Gram-negative pathogens. Although several aspects of the complex functional interactions between IncC plasmids and SGI1 have been recently deciphered regarding their conjugative transfer and incompatibility, the biological signal resulting in the hijacking of the conjugative plasmid by the integrative mobilizable element remains unknown. Here, we demonstrate that the conjugative entry of IncC/IncA plasmids is detected at an early stage by SGI1 through the transient activation of the SOS response, which induces the expression of the SGI1 master activators SgaDC, shown to play a crucial role in the complex biology between SGI1 and IncC plasmids. Besides, we developed an original tripartite conjugation approach to directly monitor SGI1 mobilization in a time-dependent manner following conjugative entry of IncC plasmids. Finally, we propose an updated biological model of the conjugative mobilization of the chromosomal resistance element SGI1 by IncC plasmids. IMPORTANCE Antimicrobial resistance has become a major public health issue, particularly with the increase of multidrug resistance (MDR) in both animal and human pathogenic bacteria and with the emergence of resistance to medically important antibiotics. The spread between bacteria of successful mobile genetic elements, such as conjugative plasmids and integrative elements conferring multidrug resistance, is the main driving force in the dissemination of acquired antibiotic resistances among Gram-negative bacteria. Broad-host-range IncC plasmids and their integrative mobilizable SGI1 counterparts contribute to the spread of critically important resistance genes (e.g., extended-spectrum β-lactamases [ESBLs] and carbapenemases). A better knowledge of the complex biology of these broad-host-range mobile elements will help us to understand the dissemination of antimicrobial resistance genes that occurred across Gammaproteobacteria borders.